Lynch syndrome–associated urothelial carcinoma: clinical and molecular findings from a single-institution cohort - A. Rametta; M. Barella; A. Scardino; F. Barbetta; E. Tamborini; F. Perrone; A. Busico; L. Agnelli; S. Rota; E. Gusmaroli; M. Stellato; A. Nuzzo; et al. (Familial Cancer, 2026)

Progress status of the NUSES Space Mission - M. Abdullahi; R. Aloisio; S. Ashurov; U. Atalay; F.C.T. Barbato; R. Battiston; M.E. Bertaina; E. Bissaldi; D. Boncioli; L. Burmistrov; I. Cagnoli; E. Casilli; et al. (Advances in Space Research, 2026)

Early effects of anti-TNFα antibodies in horses with osteoarthritis - G. Perrone; C. Giampaoli; A. Lorenzo Smirnoff; A. Ochoa; R. Pareja; E. De Simone (Journal of Equine Veterinary Science, 2025)

Mitochondrial complex I inhibition triggers NAD+-independent glucose oxidation via successive NADPH formation, “futile” fatty acid cycling, and FADH2 oxidation - Roman Abrosimov; Marius W. Baeken; Samuel Hauf; Ilka Wittig; Parvana Hajieva; Carmen E. Perrone; Bernd Moosmann (GeroScience, 2024)
Inhibition of mitochondrial complex I (NADH dehydrogenase) is the primary mechanism of the antidiabetic drug metformin and various unrelated natural toxins. Complex I inhibition can also be induced by antidiabetic PPAR agonists, and it is elicited by methionine restriction, a nutritional intervention causing resistance to diabetes and obesity. Still, a comprehensible explanation to why complex I inhibition exerts antidiabetic properties and engenders metabolic inefficiency is missing. To evaluate this issue, we have systematically reanalyzed published transcriptomic datasets from MPP-treated neurons, metformin-treated hepatocytes, and methionine-restricted rats. We found that pathways leading to NADPH formation were widely induced, together with anabolic fatty acid biosynthesis, the latter appearing highly paradoxical in a state of mitochondrial impairment. However, concomitant induction of catabolic fatty acid oxidation indicated that complex I inhibition created a “futile” cycle of fatty acid synthesis and degradation, which was anatomically distributed between adipose tissue and liver in vivo. Cofactor balance analysis unveiled that such cycling would indeed be energetically futile (-3 ATP per acetyl-CoA), though it would not be redox-futile, as it would convert NADPH into respirable FADH 2 without any net production of NADH. We conclude that inhibition of NADH dehydrogenase leads to a metabolic shift from glycolysis and the citric acid cycle (both generating NADH) towards the pentose phosphate pathway, whose product NADPH is translated 1:1 into FADH 2 by fatty acid cycling. The diabetes-resistant phenotype following hepatic and intestinal complex I inhibition is attributed to FGF21- and GDF15-dependent fat hunger signaling, which remodels adipose tissue into a glucose-metabolizing organ.

Integrated geophysical and geological surveys reveal new details of the large Montescaglioso (southern Italy) landslide of December 2013 - G. Calamita; M.R. Gallipoli; E. Gueguen; R. Sinisi; V. Summa; L. Vignola; T.A. Stabile; J. Bellanova; S. Piscitelli; A. Perrone (Engineering Geology, 2023)

Deep eutectic solvents and heterogeneous catalysis with metallic nanoparticles: A powerful partnership in sustainable synthesis - María J. Rodríguez-Álvarez; Sergio E. García-Garrido; Serena Perrone; Joaquín García-Álvarez; Vito Capriati (Current Opinion in Green and Sustainable Chemistry, 2023)

Leadership Roles in Opioid Stewardship and the Treatment of Patients with Opioid Use Disorder Among Medical Toxicologists - Joseph E. Carpenter; Brian Patrick Murray; Maryann Mazer-Amirshahi; JoAn R. Laes; Nicholas Nacca; Lewis S. Nelson; Jeanmarie Perrone; Evan S. Schwarz; Timothy J. Wiegand; Paul M. Wax (Journal of Medical Toxicology, 2020)

The microRNA-29a Modulates Serotonin 5-HT7 Receptor Expression and Its Effects on Hippocampal Neuronal Morphology - Floriana Volpicelli; L. Speranza; S. Pulcrano; R. De Gregorio; M. Crispino; C. De Sanctis; M. Leopoldo; E. Lacivita; U. di Porzio; G. C. Bellenchi; C. Perrone-Capano (Molecular Neurobiology, 2019)

Seismic performance of non-structural elements during the 2016 Central Italy earthquake - D. Perrone; P. M. Calvi; R. Nascimbene; E. C. Fischer; G. Magliulo (Bulletin of Earthquake Engineering, 2019)

Delivery of Brain-Derived Neurotrophic Factor by 3D Biocompatible Polymeric Scaffolds for Neural Tissue Engineering and Neuronal Regeneration - T. Limongi; A. Rocchi; F. Cesca; H. Tan; E. Miele; A. Giugni; M. Orlando; M. Perrone Donnorso; G. Perozziello; Fabio Benfenati; Enzo Di Fabrizio (Molecular Neurobiology, 2018)

Multimodal Neuroimaging in Schizophrenia: Description and Dissemination - C. J. Aine; H. J. Bockholt; J. R. Bustillo; J. M. Cañive; A. Caprihan; C. Gasparovic; F. M. Hanlon; J. M. Houck; R. E. Jung; J. Lauriello; J. Liu; A. R. Mayer; et al. (Neuroinformatics, 2017)

Sex differences in DNA damage produced by the carcinogen 2-acetylaminofluorene in cultured human hepatocytes compared to rat liver and cultured rat hepatocytes - Gary M. Williams; Jian-Dong Duan; Michael J. Iatropoulos; Carmen E. Perrone (Archives of Toxicology, 2016)

Spin-off Extreme Value and Archimedean copulas for estimating the bivariate structural risk - R. Pappadà; E. Perrone; F. Durante; G. Salvadori (Stochastic Environmental Research and Risk Assessment, 2016)

Determination of aerosol deliquescence and crystallization relative humidity for energy saving in free-cooled data centers - L. Ferrero; L. D’Angelo; G. Rovelli; G. Sangiorgi; M. G. Perrone; M. Moscatelli; M. Casati; V. Rozzoni; E. Bolzacchini (International Journal of Environmental Science and Technology, 2015)

The Monviso Massif and the Cottian Alps as Symbols of the Alpine Chain and Geological Heritage in Piemonte, Italy - Franco Rolfo; Piera Benna; Paola Cadoppi; Daniele Castelli; Sergio E. Favero-Longo; Marco Giardino; Gianni Balestro; Elena Belluso; Alessandro Borghi; Fernando Cámara; Roberto Compagnoni; Simona Ferrando; et al. (Geoheritage, 2015)

Prevalence of respiratory colonisations and related antibiotic resistances among paediatric tracheostomised patients of a long-term rehabilitation centre in Italy - M. Pozzi; P. Pellegrino; S. Galbiati; M. Granziera; F. Locatelli; C. Carnovale; V. Perrone; S. Antoniazzi; C. Perrotta; S. Strazzer; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Epidemiological analysis on two decades of hospitalisations for meningitis in the United States - P. Pellegrino; C. Carnovale; V. Perrone; D. Salvati; M. Gentili; T. Brusadelli; S. Antoniazzi; M. Pozzi; S. Radice; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Semivolatile PAH and n-alkane gas/particle partitioning using the dual model: up-to-date coefficients and comparison with experimental data - G. Sangiorgi; L. Ferrero; M. G. Perrone; E. Papa; E. Bolzacchini (Environmental Science and Pollution Research, 2014)

Cystic fibrosis Δf508 mutation screening in Brazilian women with altered fertility - G. V. F. Brunoro; E. V. Wolfgramm; I. D. Louro; I. I. Degasperi; V. C. W. Busatto; A. M. S. Perrone; M. C. P. Batitucci (Molecular Biology Reports, 2011)

Coronary computerized tomography angiography for rapid discharge of low-risk patients with cocaine-associated chest pain - Kristy M. Walsh; Anna Marie Chang; Jeanmarie Perrone; Christine M. McCusker; Frances S. Shofer; Mark J. Collin; Harold I. Litt; Judd E. Hollander (Journal of Medical Toxicology, 2009)

Phosphorus Dynamics in a Small Eutrophic Italian Lake - U. Perrone; A. Facchinelli; E. Sacchi (Water, Air, & Soil Pollution, 2008)

A Biomonitoring Study Assessing the Residual Biological Effects of Pollution Caused by the HAVEN Wreck on Marine Organisms in the Ligurian Sea (Italy) - A. Viarengo; F. Dondero; D. M. Pampanin; R. Fabbri; E. Poggi; M. Malizia; C. Bolognesi; E. Perrone; E. Gollo; G. P. Cossa (Archives of Environmental Contamination and Toxicology, 2007)

Developmental morphology of Acanthophora nayadiformis (Rhodophyta, Ceramiales): Sympodial growth and propagule germination - C. Perrone; E. Cecere; C. I. Delle Foglie (Plant Biosystems, 2005)

Embryonic turkey liver: activities of biotransformation enzymes and activation of DNA-reactive carcinogens - Carmen E. Perrone; Hans-Juergen Ahr; Jian Dong Duan; Alan M. Jeffrey; Ulrich Schmidt; Gary M. Williams; Harald H. Enzmann (Archives of Toxicology, 2004)